Development of a geographical information system for risk mapping of reinforced concrete buildings subjected to atmospheric corrosion in Cyprus using optical remote sensing data - Neocleous, Kyriacos; Agapiou, Athos; Christofe, Andreas; Themistocleous, Kyriacos; Achillides, Zenon; Panayiotou, Marilia; Hadjimitsis, Diofantos G. (My University, 2014)
Concrete reinforced with steel rebars remains one of the most widely used construction materials. Despite its excellent mechanical performance and expected service life of at least 50 years, reinforced concrete is subjected to corrosion of the steel rebars which normally leads to concrete spalling, deterioration of the reinforced concrete’s (RC) mechanical properties and eventual reduction of the structural load capacity. In Cyprus, especially in coastal regions where almost 60% of the population resides, many structural problems have been identified in RC structures, which are mainly caused by the severe corrosion of steel rebars. Most RC buildings, located in coastal areas, show signs of corrosion within the first 15-20 years of their service life and this affects their structural integrity and reliability, especially against seismic loading. This paper presents the research undertaken as part of the STEELCOR project which aims to extensively evaluate the steel corrosion of RC buildings in coastal areas of Cyprus and conduct a risk assessment relating to steel corrosion. Non-destructive testing of corroded RC structures measurements were used to estimate the simplified index of structural damage. These indices were imported into a Geographical Information System to develop a digital structural integrity map of Cyprus which would show the areas with high risk of steel corrosion of RC buildings. In addition, archive optical remote sensing dataset was used to map the urban expansion footprint during the last 30 years in Cyprus with the aim of undertaking corrosion risk scenarios by utilizing the estimated indices. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: Buildings; Corrosion; Remote sensing; Nondestructive evaluation; Reliability